Fungal Infection following Total Elbow Arthroplasty - Samuel S. Ornell; Khang H. Dang; Aaron J. Bois; Anil K. Dutta (Case Reports in Orthopedics)
A specific treatment protocol for managing fungal infections after total elbow arthroplasty (TEA) does not currently exist. The purpose of this report is to describe our experience and outline our treatment algorithm for a rare case of prosthetic joint infection (PJI) following a TEA. We present a case of a PJI due to Candida parapsilosis after TEA in a 57 year-old Caucasian woman with a history of hypertension, depression, and three previous surgical procedures to the affected limb. A fungal PJI by the organism C. parapsilosis following TEA has not been previously reported. Successful eradication of the fungal infection was achieved utilizing resection arthroplasty; placement of an amphotericin, vancomycin, and tobramycin-impregnated cement spacer; and 6 months of organism-specific antifungal medication. Although the patient was clinically ready for reimplantation, she passed away due to unrelated issues before reimplantation could be performed. While PJI is a devastating complication following TEA, a fungal infection is a rare complication that imposes difficult challenges to the treating surgeon. With our case report, we hope to contribute to the overall knowledge of fungal infections associated with TEA and describe our successful treatment of this complex case.